The Effects of Psychological Distance on the Diagnosticity of Digits to the Left Versus Right of a Separator - Yan, Dengfeng; Vijayakumar, Suhas; Hong, Jiewen (Journal of Marketing Research, 2024)
Many numerical expressions contain a separator such as a comma (e.g., 1,234) or a decimal point (e.g., 12.34) that divides the number into left and right parts. This research examines how individuals compare such numbers as a function of psychological distance. Integrating insights from research on diagnosticity, numerical cognition, and mental construal, the authors hypothesize that as psychological distance increases, the perceived diagnosticity of digits to the right of a separator (hereinafter “right digits”) decreases faster than that of the digits to the left of a separator (hereinafter “left digits”), which leads individuals to assign less weight to the right digits in comparative judgment. Four studies offer triangulating support for this theorizing and the underlying mechanism. In addition, the authors show that this effect is attenuated or suppressed when individuals perceive that numerical ratings are more stable over time (thereby increasing the perceived diagnosticity of right digits; Study 3) and when the distinction between left and right digits is made less obvious (e.g., when removing the digit separator; Study 4). This research offers additional nuance to our understanding of numerical cognition and how psychological distance influences the processing of different types of information.